2015
DOI: 10.1590/1983-084x/13_052
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of leaves of Piper species display larvicidal activity against the dengue vector, Aedes aegypti (Diptera: Culicidae)

Abstract: ABSTRACT:The mosquito Aedes aegypti is the vector of the dengue virus, an endemic arbovirus from tropical and subtropical regions of the world. The increasing resistance of mosquitoes to commercial insecticides impairs regular control programs; therefore, chemical prospecting originating from the Amazonian flora is promising for potential new insecticides. Several Piper species are, notably, rich in phenylpropanoids and terpenoids, substances with proven insecticidal activity. The composition and the larvicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 11 publications
0
34
1
3
Order By: Relevance
“…Phenylpropanoid apiol is one of the major components of essential oil from P. aduncum (Santana et al 2015).…”
Section: Phytochemical Analysis Of P Aduncummentioning
confidence: 99%
See 2 more Smart Citations
“…Phenylpropanoid apiol is one of the major components of essential oil from P. aduncum (Santana et al 2015).…”
Section: Phytochemical Analysis Of P Aduncummentioning
confidence: 99%
“…These compounds derived from phenylalanine are present in most plant of the Piperaceae family. Several authors have found that these plant species have insecticidal and acaricidal activity (Salgado et al 2012, Souto et al 2012, Trindade et al 2012, Lima et al 2014, Santana et al 2015). …”
Section: Insecticidal Activity Of Hexane Ethyl Acetate and Ethanol mentioning
confidence: 99%
See 1 more Smart Citation
“…solmsianum, P. amalago, P. Hispidum, and P. umbellatum (Table 4). Apparently, these compounds are common among Piperaceae, as observed in other chemical constitutions of several Piper species (Santos, Moreira, Guimarães, & Kaplan, 2001;Mundina et al, 2001;Cruz, Cáceres, Álvarez, Apel, & Henriques, 2011;Santana et al, 2015).…”
Section: Discussionmentioning
confidence: 73%
“…Piper aduncum and P. marginatum presented compounds already reported as insecticides in previous works, such as dillapiol, asaricine (sarisan), piperitone and myristicin (Bizzo et al, 2001;Morais et al, 2007;Qin, Huang, Li, Chen, & Peng, 2010;Souto et al, 2012;Santana et al, 2015;Ribeiro, Camara, & Ramos, 2016;Krinski & Foerster, 2016). For P. caldense, P. fuligineum, P. Mollicomum, and P. mosenii, there are no studies regarding the insecticidal activity, and our work is the first to test the ovicidal activity against a lepidopteran pest of importance in Brazilian agriculture.…”
Section: Discussionmentioning
confidence: 82%